The Position of The Defendant’s Statement as Evidence in The Perpective of Islamic Criminal Justice - Nurul Hidayah Ritonga; Zulkarnain (JUSTITIA JURNAL HUKUM, 2025)
This study raises legal issues regarding the position and strength of defendant testimony as evidence in criminal cases through a comparative approach between the Indonesian criminal law system and Islamic criminal law. The purpose of this study is to examine the fundamental differences in the assessment of defendant testimony in both legal systems. The research method used is normative juridical. The results of the study show that in Indonesian criminal law, the defendant's testimony as regulated in the Criminal Procedure Code (KUHAP) has the weakest position and can only be used as a basis for evidence if it is supported by at least two other valid pieces of evidence, in accordance with the provisions of Article 183 of the Criminal Procedure Code. Conversely, in Islamic criminal law, the defendant's testimony (iqrar) can be strong evidence and stand alone as perfect evidence, especially in ta'zir cases. However, in hudud and qishash-diyat cases, the confession must meet strict requirements, such as being made voluntarily, in detail, and repeatedly, as well as considering the consent of the victim's heirs in qishash cases. This comparison shows that despite differences in the weight of evidence, both systems place the principles of prudence and justice as the basis for assessing the defendant's statement to ensure the achievement of material truth. These findings contribute to the development of a criminal evidence system based on substantive justice and principles.